Work in the Experience of Persons with Intellectual Disabilities. A Focus Group Research Report - Bartnikowska, Urszula; Ćwirynkało, Katarzyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Although the literature recognizes the benefits of work and employment for people with intellectual disabilities, there is little research devoted to their experiences presented from their own perspective. This article is a report on a phenomenographic focus study conducted in four groups of adults with moderate or mild intellectual disabilities. The main aim of the research was to understand the experiences of adults with intellectual disabilities related to work and employment and the meanings given to them. A total of 34 people took part in the research. As a result of the analysis, three areas were identified to which the participants referred when talking about work and employment: (1) their own person – dreams, expectations, imaginations, opportunities, beliefs, and experiences, (2) the environment – environmental patterns, support and barriers, recruitment for work and labour market opportunities, and (3) meanings given to work – a source of income / fulfilling material, social, emotional needs (satisfaction) and an opportunity for self-development / self-realization. The obtained findings have important implications for families, practitioners, and social policy regarding the employment of individuals with intellectual disabilities.